Understanding Reference: Morphological Marking in Japanese - Shinichi SHOJI (Acta Linguistica Asiatica, 2017)
This study investigates reference resolution with repeated-name anaphors in Japanese, particularly focusing on (i) subject anaphor with the nominative postposition ga, (ii) topic-subject anaphor with the topic postposition wa, (iii) scrambled object anaphor with the accusative postposition o, and (iv) topic-object anaphor with the topic postposition wa. A self-paced sentence-by-sentence reading experiment was conducted using two-sentence discourse items followed by comprehension questions, aiming to examine which type of anaphor would trigger a faster realization of the anaphor-antecedent relationship. The discourse items included antecedents in the first sentence and anaphors in the second sentences, and the comprehension questions asked about the antecedents in the first sentences. Results showed that the comprehension questions for the discourses that included topic anaphors (topic-subject-wa and topic-object-wa) were responded to faster than those for the discourses that included non-topic anaphors (subject-ga and scrambled object-o). The results indicate that anaphors’ topic-hood given by wa facilitates the realization of antecedents.